NCT Dream, Tap Cash BNI, dan Minat Beli Komunitas NCTzen - Rini, Cika Puspita; Yoedtadi, Moehammad Gafar (Prologia, 2025)
The rise of the Korean Wave throughout the world, including in Indonesia, means companies have a great opportunity to attract consumers who are enthusiastic about K-Pop. One of the business strategies taken is to make K-Pop idol groups as models or Brand Ambassadors. An example is the collaboration between the boy group NCT Dream and Tap Cash BNI in Indonesia, which is the author's research. This research aims to determine the influence of NCT Dream as BNI's Tap Cash model on the purchasing interest of their fan community, NCTzen, in Indonesia. The research method used was quantitative by conducting a survey using a questionnaire distributed to 100 respondents who were members of the NCTzen community in Jakarta WhatsApp NCTzen – Jakarta under the auspices of KLY (KapanLagi Youniverse). Data analysis was carried out using validity tests, T tests, simple linear regression analysis, and coefficient of determination using SPSS Statistics 26. The results of the analysis show that as much as 85.7% of the variation in buying interest of NCTzen community members can be explained by the influence of NCT Dream as BNI's Tap Cash model. The remaining 14.3% was influenced by other variables not examined in this study. This research contributes to understanding the relationship between the K-Pop music industry and marketing communications through the use of K-Pop idols as models. Maraknya Korean Wave di seluruh dunia, termasuk di Indonesia membuat perusahaan memiliki peluang besar untuk menarik konsumen yang antusias terhadap K-Pop. Salah satu strategi bisnis yang diambil adalah menjadikan grup idol K-Pop sebagai model atau Brand Ambassador. Contohnya adalah kolaborasi antara boy group NCT Dream dan Tap Cash BNI di Indonesia yang merupakan penelitian penulis. Penelitian ini bertujuan untuk mengetahui pengaruh NCT Dream sebagai model Tap Cash BNI terhadap minat beli komunitas penggemar mereka, NCTzen, di Indonesia. Metode penelitian yang digunakan adalah kuantitatif dengan melakukan survei menggunakan kuesioner yang disebarkan kepada 100 responden anggota komunitas NCTzen di Jakarta WhatsApp NCTzen – Jakarta dibawah naungan KLY (KapanLagi Youniverse). Analisis data dilakukan dengan menggunakan uji validitas, uji T, analisis regresi linier sederhana, dan koefisien determinasi menggunakan SPSS Statistic 26. Hasil analisis menunjukkan bahwa sebanyak 85.7% dari variasi minat beli anggota komunitas NCTzen dapat dijelaskan oleh pengaruh NCT Dream sebagai model Tap Cash BNI. Sisanya, 14.3%, dipengaruhi oleh variabel lain yang tidak diteliti dalam penelitian ini. Penelitian ini memberikan kontribusi dalam memahami keterkaitan antara industri musik K-Pop dan komunikasi pemasaran melalui penggunaan idol K-Pop sebagai model.